2004
DOI: 10.1093/geront/44.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Innovative Medicare Managed Care Program on the Quality of Care for Nursing Home Residents

Abstract: Evercare, with its use of nurse practitioners, represents a model that can provide more efficient care that is of at least comparable quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 18 publications
2
85
0
Order By: Relevance
“…30 The Evercare model of capitated payments and the assignment of a nurse practitioner to oversee the care of frail nursing home residents were shown to result in fewer hospitalizations and saved $103,000 per nurse practitioner in hospital costs. 12,13 The savings with the Evercare model were achieved with survival and quality outcomes that were similar to those with conventional care.…”
Section: Discussionmentioning
confidence: 91%
“…30 The Evercare model of capitated payments and the assignment of a nurse practitioner to oversee the care of frail nursing home residents were shown to result in fewer hospitalizations and saved $103,000 per nurse practitioner in hospital costs. 12,13 The savings with the Evercare model were achieved with survival and quality outcomes that were similar to those with conventional care.…”
Section: Discussionmentioning
confidence: 91%
“…The majority (n = 24) were retrospective. Five studies reported on an intervention or a strategy for reducing transfers to acute care (information not shown in the table) [21,23,26,27,30,38]. …”
Section: Resultsmentioning
confidence: 99%
“…Lessons from national, state, and provider-led initiatives to integrate acute and LTC suggest that decreasing preventable acute care hospitalizations for this population is a desirable and achievable strategy (R. L. Kane, Flood, Bershadsky, & Keckhafer, 2004;R. L. Kane, Keckhafer, Flood, Bershadsky, & Siadaty, 2003).…”
Section: Decreasing Preventable Acute Care Hospitalizationsmentioning
confidence: 99%